08.41: Renewal method for aged steel bridges with polymer cement mortar. (13th September 2017) - Taniguchi, Nozomu; Satake, Shinya; Lin, Weiwei; Hiroe, Masaaki; Kubo, Takeaki
ABSTRACT: This research offers a new composite‐revamping method for railway bridges by assuming composite remodelling process of existing steel bridges having no specific fissure damages or serious corrosions and effectively making use of relatively new materials to it. Effects of noise reduction and improved stiffness were further confirmed through Impact tests (vibration and noise measurement tests) in order to prove the efficacy of the composite remodelling. By the tests, it can be confirmed that the composite structuring work tended to reduce the vibration level by around 10 to 35 dB and the all pass (AP) value by about 30 dB. In addition, the stiffness increases from the bridges of only steel members. The remainder life of the structure is extended by this effect. These effects are confirmed by the experiments for railway bridges.